Load characteristic analysis of a double-side internal coreless stator axial flux PMG - Ketut Wirtayasa; Pudji Irasari; Muhammad Kasim; Puji Widiyanto; Muhammad Fathul Hikmawan (National Research and Innovation Agency, 2019)
The main issue of using a permanent magnet in electric machines is the presence of cogging torque. Several methods have been introduced to eliminate it, one of which is by employing a coreless stator. In this paper, the load characteristic analysis of the double-side internal coreless stator axial flux permanent magnet generator with the specification of 1 kW, 220 V, 50 Hz, 300 rpm and 1 phase is discussed. The purpose is to learn the effect of the load to the generator performance, particularly the output power, efficiency and voltage regulation. The design and analysis are conducted analytically and numerically with two types of simulated loads, pure resistive and resistive-inductive in series. Each type of load provides power factor 1 and 0.85 respectively. The simulation results show that when loaded with resistive load, the generator gives a better performance at the output power (1,241 W) and efficiency (91 %), whereas a better voltage regulator (5.86 %) is achieved when it is loaded with impedance. Since the difference in the value of each parameter being compared is relatively small, it can be concluded that the generator represents good performance in both loads.